2009
DOI: 10.1523/jneurosci.2574-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Reweighting of Visual and Vestibular Cues during Self-Motion Perception

Abstract: The perception of self-motion direction, or heading, relies on integration of multiple sensory cues, especially from the visual and vestibular systems. However, the reliability of sensory information can vary rapidly and unpredictably, and it remains unclear how the brain integrates multiple sensory signals given this dynamic uncertainty. Human psychophysical studies have shown that observers combine cues by weighting them in proportion to their reliability, consistent with statistically optimal integration sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

45
476
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 372 publications
(527 citation statements)
references
References 63 publications
(121 reference statements)
45
476
6
Order By: Relevance
“…This estimate can be used to extract the inertial and gravitational components of the otolith afferent signals, in agreement with previous studies (Angelaki et al, , 2002(Angelaki et al, , 2004Merfeld et al, 1999). Our analysis suggests that conflicting motion signals are resolved by a process of optimal estimation, similar as shown in numerous previous studies (Ernst and Banks, 2002;Weiss et al, 2002;MacNeilage et al, 2007;Angelaki et al, 2009;Fetsch et al, 2009) as well as in modeling work on vestibular information processing (Laurens et al, 2007. By demonstrating that the brain effectively uses geometrically consistent three-dimensional representations, this study supports the notion that the internal model hypothesis as formulated in the general context of motor control (Ito, 1989;Kawato, 1999;Davidson and Wolpert, 2005) is also an important concept for understanding how the brain solves spatial orientation problems.…”
Section: Discussionsupporting
confidence: 91%
“…This estimate can be used to extract the inertial and gravitational components of the otolith afferent signals, in agreement with previous studies (Angelaki et al, , 2002(Angelaki et al, , 2004Merfeld et al, 1999). Our analysis suggests that conflicting motion signals are resolved by a process of optimal estimation, similar as shown in numerous previous studies (Ernst and Banks, 2002;Weiss et al, 2002;MacNeilage et al, 2007;Angelaki et al, 2009;Fetsch et al, 2009) as well as in modeling work on vestibular information processing (Laurens et al, 2007. By demonstrating that the brain effectively uses geometrically consistent three-dimensional representations, this study supports the notion that the internal model hypothesis as formulated in the general context of motor control (Ito, 1989;Kawato, 1999;Davidson and Wolpert, 2005) is also an important concept for understanding how the brain solves spatial orientation problems.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, empirically measured heading discrimination thresholds during combined vestibular -visual heading perception were close to the predictions produced by a statistically optimal cue combination rule (Gu et al 2008;Fetsch et al 2009Fetsch et al , 2011Fetsch et al , 2013Butler et al 2010Butler et al , 2015de Winkel et al 2013). …”
Section: Multisensory Integration Improves Perceptual Precisionsupporting
confidence: 67%
“…Psychophysical studies of heading discrimination using two-alternative forcedchoice tasks have reported vestibular heading discrimination thresholds in darkness that are as small as a few degrees Fetsch et al 2009;Butler et al 2010Butler et al , 2015de Winkel et al 2010;Drugowitsch et al 2014). Such threshold values are comparable (although larger) with those described in visual heading discrimi-nation tasks (Warren and Hannon 1990;Royden et al 1992;van den Berg and Brenner 1994;Stone and Perrone 1997).…”
Section: Multisensory Cues For Heading Perceptionmentioning
confidence: 82%
See 1 more Smart Citation
“…Birds have large regions of the brain dedicated to visual processing, suggesting parallels with insects, such as a leading role for optic flow in controlling flight paths (2,3). It has recently been demonstrated that birds exhibit visually mediated position control much like bees (4,5), even though they have complex spatial mapping in the hippocampal formation (6), and a much larger brain for interpreting visual input and dynamically integrating vision with proprioceptive and vestibular feedback (7)(8)(9).…”
mentioning
confidence: 99%